Improving the self-care behavior of type 2 diabetes mellitus clients by combining the basic conditioning factors and self-care agency - Minarti; Supriyanto; Dinata, Ach. Arfan; Windi, Yohanes; Yumni, Hilmi; Miadi (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Type 2 diabetes mellitus (T2DM) is a chronic disease that requires active participation of the person to perform self-care. Self-care behavior requires various drivers to perform effectively. This study aims to investigate how the basic conditioning factors (BCF) and self-care agency (SCA) improve the self-care behavior (SCB) of T2DM clients.  Methods: This is a cross-sectional study that involved 195 T2DM clients who were selected through convenience sampling from three public health centers (PHCs) in Surabaya. Questionnaires were used to gather information on basic conditioning factors (i.e. developmental status, health services, sociocultural, family support, lifestyle, and environment) and self-care agency (diet, blood sugar monitoring, physical exercise, treatment, and foot care) For self-care behavior, we adopted the American Association of Diabetes Educators variables including healthy eating, being active, monitoring, taking medications, problem-solving, healthy coping, and reducing risks. We conducted the Structural Equation Modelling Smart PLS (SEM) Version 3.0 to analyze the interaction of sub-variables of BCF and SCA that improve the SCB. Results: The development status, health status, sociocultural, family, and lifestyle indirectly (where SCA becomes the intermediate factor) influence the improvement of SCB among T2DM clients. Lifestyle and environmental factors of SCA are the sub-variables that directly improve the SCB of T2DM clients.  Conclusion: The study concludes that some sub-variables of basic conditioning factors and self-care agency are influential in improving the quality of self-care practice of T2DM sufferers. It is advised that empowering T2DM clients to perform effective self-care management requires drivers from BCF and SCA factors.